Complement's favourite organelle—Mitochondria?. (28th September 2020) - Rahman, Jubayer; Singh, Parul; Merle, Nicolas S.; Niyonzima, Nathalie; Kemper, Claudia
Abstract : The complement system, well known for its central role in innate immunity, is currently emerging as an unexpected, cell‐autonomous, orchestrator of normal cell physiology. Specifically, an intracellularly active complement system—the complosome—controls key pathways of normal cell metabolism during immune cell homeostasis and effector function. So far, we know little about the exact structure and localization of intracellular complement components within and among cells. A common scheme, however, is that they operate in crosstalk with other intracellular immune sensors, such as inflammasomes, and that they impact on the activity of key subcellular compartments. Among cell compartments, mitochondria appear to have built a particularly early and strong relationship with the complosome and extracellularly active complement—not surprising in view of the strong impact of the complosome on metabolism. In this review, we will hence summarize the current knowledge about the close complosome–mitochondria relationship and also discuss key questions surrounding this novel research area. Linked Articles: This article is part of a themed issue on Canonical and non‐canonical functions of the complement system in health and disease. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.14/issuetoc